Non-communicable diseases and tuberculosis: Anticipating the impending global storm. Issue 9 (2nd September 2019) - Puchner, Karl Philipp; Rodriguez-Fernandez, Rodrigo; Oliver, Matthew; Solomos, Zisimangelos
ABSTRACT: The epidemiological transitions that have occurred in low and middle income countries (LMIC) during the past decades have led to an increased prevalence on non-communicable diseases (NCDs) in these countries, where the burden of infectious diseases (IDs), especially tuberculosis (TB), remains high. Although the true dimensions of this comorbidity have not yet been fully understood, there is a growing amount of data, over the last 10 years, that suggest a clear association between NCDs and TB. In particular, there is a continuously increasing body of evidence that diabetes mellitus, chronic respiratory conditions, tobacco use, mental health illnesses and chronic kidney disease increase TB morbidity and mortality and vice versa. This bidirectional negative association between diseases may jeopardise the achievement of the Sustainable Development Goals (SDGs) specific TB targets, thus underlying the importance of integrated public health responses towards both epidemics. Population as well as individual based approaches are required, along with both strategic and operation integration on a global scale. This year's United Nations High Level Meetings (ΗLMs) presented a rare opportunity for the political foundations of the TB and NCD responses to be dug together, thus creating a potential breakthrough in the global response to both epidemics.